PKM Pelatihan Integrasi Kompetensi Religius Kepada Guru Bahasa Indonesia di Kabupaten Majene - Muhammad Saleh; Sulastriningsih Djumingin; Mayong Mayong (Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract: The partner of this Community Partnership Program (PKM) is an Indonesian teachers in Majene Regency. The problems are: (1) How do teachers prepare Learning Implementation Plans (RPP) with the design of the integration model of religious competence in Indonesian language learning, (2) How do teachers apply the Learning Implementation Plans (RPP) with the integration model of religious competence in Indonesian language learning, (3) How far is the teacher's ability to carry out Indonesian language learning using the integration model of religious competence. The methods used are lectures, demonstrations, discussions, questions and answers, and mentoring partners. The results achieved are: (1) Partners have knowledge about preparing a Learning Implementation Plan (RPP) with a religious competency integration model design in Indonesian language learning, (2) Partners implement a Learning Implementation Plan (RPP) with a religious competency integration model in language learning learning Indonesia (3) Partners are able to carry out Indonesian language learning using the integration model of religious competence.Keywords: competence, integrity, religious, teacher